2023
DOI: 10.1186/s10020-023-00638-1
|View full text |Cite|
|
Sign up to set email alerts
|

RhoA promotes osteoclastogenesis and regulates bone remodeling through mTOR-NFATc1 signaling

Abstract: Background The cytoskeletal architecture of osteoclasts (OCs) and bone resorption activity must be appropriately controlled for proper bone remodeling, which is associated with osteoporosis. The RhoA protein of GTPase plays a regulatory role in cytoskeletal components and contributes to osteoclast adhesion, podosome positioning, and differentiation. Although osteoclast investigations have traditionally been performed by in vitro analysis, however, the results have been inconsistent, and the sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Conditional knockout of RhoA in osteoclast lineage mice was found to cause a severe osteopetrosis phenotype, likely due to the inhibition of osteoclast formation (Wang et al, 2023). In our study, we revealed Myosins, motor proteins, play a crucial role in the formation and rearrangement of F-actin rings.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Conditional knockout of RhoA in osteoclast lineage mice was found to cause a severe osteopetrosis phenotype, likely due to the inhibition of osteoclast formation (Wang et al, 2023). In our study, we revealed Myosins, motor proteins, play a crucial role in the formation and rearrangement of F-actin rings.…”
Section: Discussionmentioning
confidence: 55%
“…By contrast, other studies have shown that RhoA promoted osteoclastogenesis. Conditional knockout of RhoA in osteoclast lineage mice was found to cause a severe osteopetrosis phenotype, likely due to the inhibition of osteoclast formation (Wang et al, 2023). In our study, we revealed that both RhoA inhibitor C3 and siRNA‐mediated knockdown of RhoA in mBMMs decreased the mRNA expression of NFATc1 and reduced OC formation (Figure 6d–i).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mature osteoclasts MERTK signaling inhibited osteoclast podosome ring formation. Other authors showed that RHOA enhances osteoclastogenesis via mTOR-Nfatc1 and conditional knockout of RHOA resulted in increased bone mass 42,43 . In contrast, another study showed that activation of RHOA led to podosome belt dissolution and microtubule deacetylation thereby inhibiting osteoclast maturation 38 .…”
Section: Discussionmentioning
confidence: 99%